Co-operation between large enterprises (LE’s) and SME’s: an approach to overcome the stage internationalization process - Dias, Eurico; Lopes, Daniel Serra (Business: Theory and Practice, 2014)
Many companies are using their networks in order to overcome psychic distance – liability of foreignness – and liability of outsidership; and networks at domestic markets can be a base in which SMEs can find a lever to get a rapid internationalization process. Regarding this topic has been developed a case study in the Polish market, where a local retailer (“Biedronka”) owned by a Portuguese group (“Jerónimo Martins”) is offering Portuguese products. In order to apply a constructivist methodology, using the case study method, five SMEs where selected in order to understand if co-operation between these companies and a LE (Large Enterprise) would be a way in order to overcome the liability of foreignness and the liability of outsidership. It was also our purpose the understanding of which are the main issues that promote insidership and also the promotion of a rapid internationalization. Our conclusions have shown a LE as a source of institutional and market-specific knowledge, and regarding this last type of knowledge, as source of opportunities, and also how a SME with internationalization knowledge, an international focus and adaptation skills (in order to adapt products and prices) can introduce in a co-operative international venture, in far psychic markets, the ingredients needed to get a successful and rapid entry in a foreign market. Trust as a resource, accumulated during lasting relationships in the domestic market, has been shown as a basic requirement to develop these co-operative approaches in international markets.